Immunity and the Public/Private Boundary in EU Employment Law. Issue 1 (March 2015) - Rodgers, Lisa
The doctrine of 'immunity', whether considered in terms of state immunity (the immunity of the state against claims by embassy employees), or diplomatic immunity (the immunity of diplomatic agents against claims by their own employed staff) acts to block employment law claims and therefore prevent access to justice for certain employment law groups. This article discusses recent developments in the doctrine of immunity in the context of the jurisdictional scope of EU (employment) law. In particular, it considers two recent trends in the development of the immunity doctrine. The first trend is the erosion of the 'absolute' nature of state immunity and an increased willingness at both EU and national (UK) levels to consider state immunity as just one factor in the 'balancing' exercise associated with human rights. The second trend considered in this article is that associated with diplomatic immunity. Whilst there have been signs of a relaxation of the strict operation of this doctrine in some cases, there is also evidence of a judicial reluctance to erode diplomatic immunity in others. The article discusses the arguments put forward in both (state and diplomatic immunity) cases, and particularly what they reveal about the current understanding of the jurisdictional scope and public/private divide in EU employment law.